KEANEKARAGAMAN EPIFIT BERPEMBULUH PADA BATANG POHON INANG ANGIOSPERMAE DAN GYMNOSPERMAE DI KEBUN RAYA CIBODAS - Aditiya Nurrahma; Ismanto .; Taufikurrahman Nasution (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2022)
Epiphytes are types of plants that attach and grow on other plants to obtain sunlight, water, air, and minerals for their growth. The aim of this study are knowing the diversity of vascular  epiphytes on the host trunks of Angiosperms and Gymnosperms, knowing the differences in vascular epiphytic communities on the host trunks of Angiosperms and Gymnosperms and to determine factors causing vascular epiphytes communities on the host trunk is used in this research. Sampling plot is located on the host tree's trunk to facilitate the calculation of vascular epiphytes; a simple plot measuring 2 m x 0,5 m was made facing east and west. Determination of the number of tree sampling is done based on the Area Species Curve. The results of this study indicate that the vascular epiphyte diversity on trunks of Gymnospermae is higher than Angiospermae, meanwhile that Shannon Wiener diversity index of vascular epiphytes on Angiosperms and Gymnosperms host trunks being moderate category. Jaccard Similarity index  was 0.44 and indicated the different of epiphytes community between  Angiospermae and Gymnospermae tree host. The dominant species based on Important value index in Angiosperms are Davallia hymenophylloides (35,05%), Goniophlebium subauriculatum (20,92%), and Dendrobium mutabile (20,07) while ini Gymnosperme are Davallia hymenophylloides (41,36%), Goniophlebium subauriculatum (15,94%), and Peperomia tetraphylla (15,55%). In Angiospermae, the factors that influence the diversity of vascular epiphyte species are roughness and thickness, while in Gymnosperms the influential factors are roughness and diameter.